Multi-technique characterization of various artefacts and raw materials from Old Nisa (Turkmenistan): A preliminary study. (February 2016) - Turco, F.; Davit, P.; Borghi, A.; Bruno, J.; Lippolis, C.; Operti, L.
Abstract: A multitechnique (SEM-EDX, XRD, TGA) characterization was performed on several materials and artefacts from Old Nisa excavated during the recent Italian–Turkmen archaeological expedition, which involved a large building in the SW corner of the citadel, formed by rooms utilized as warehouses and workshops. Polygenic conglomerates archaeologically classified as anhydrites were examined and proved to be highly compatible with all the studied architectural artefacts (a plaster, a mortar, and a mould), making strongly plausible their identification as raw materials. Besides, several pigments at different stages of the manufacturing process were examined. A very complex situation emerged, suggesting the existence of different productive processes. At last, a black cylindrical object, identified as a seal, but almost completely devoid of engravings, turned out to be made of graphite and obtained by turning. The results of the analyses on these materials shed a new light on the complexity of the manufacturing processes carried out in Old Nisa in connection with the production of decorative elements for the monumental complex located inside the citadel. Highlights: Evaluation of the technology of production of various architectural elements in Old Nisa Complex situation emerging from the pigment manufacturing technology assessment A graphite seal: a very peculiar material for a not entirely explained object Improved understanding of production technologies and raw materials used in the Parthian period in Old Nisa